The daily lives of Muslims Islam and public confrontation in contemporary Europe - Göle, Nilüfer 1953- (Zed Books, 2017)
In The Daily Lives of Muslims, Nilufer Goele provides an urgently needed corrective to this distorted image of Islam. Engaging with Muslim communities in twenty-one cities across Europe where controversies over integration have arisen - from the banning of the veil in France to debates surrounding sharia law in the UK - the book brings the voices of this neglected majority into the debate. In doing so, Goele uncovers a sincere desire among many Muslims to participate in the public sphere, a desire which is too often stifled by Western insecurity and attempts to suppress the outward signs of religious differenc